2018
DOI: 10.1515/jomb-2017-0042
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Deaminase 1 as a Biomarker for Diagnosis and Monitoring of Patients with Acute Lymphoblastic Leukemia

Abstract: SummaryBackgroundAcute lymphoblastic leukemia (ALL) is known as the most prevalent pediatric malignancy all around the world. Identification of specific biomarker is necessary for early diagnosis and effective therapy. It is believed that Adenosine deaminase (ADA) as an enzyme involved in the purine salvage pathway increases in ALL patients. Herein, the quantity and pattern of ADA isoenzymes were surveyed among ALL patients in comparison to healthy subjects.MethodsSerum and RBC samples of three different group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…An association of serum adenosine deaminase with systemic inflammation is observed in experimental colitis, 23 and serum adenosine deaminase activity is elevated in inflammatory diseases such as acute lymphoblastic leukemia, autoimmune hepatitis and rheumatic disease. [24][25][26][27] Serum adenosine deaminase has been reported to be an inflammatory marker in rheumatoid arthritis. 28 In another study showed that serum adenosine deaminase, an endogenous anti-inflammatory metabolite, is elevated in response to inflammatory status resulted by adipose tissue in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…An association of serum adenosine deaminase with systemic inflammation is observed in experimental colitis, 23 and serum adenosine deaminase activity is elevated in inflammatory diseases such as acute lymphoblastic leukemia, autoimmune hepatitis and rheumatic disease. [24][25][26][27] Serum adenosine deaminase has been reported to be an inflammatory marker in rheumatoid arthritis. 28 In another study showed that serum adenosine deaminase, an endogenous anti-inflammatory metabolite, is elevated in response to inflammatory status resulted by adipose tissue in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…According to Moorthy et al [54], elevated activity of AHH is essential in B(a)P metabolism, as it is the main enzyme responsible for B(a)P conversion to the extremely active benzo[a]pyren-7,8-dihydrodiol-9,10-epoxide, which is associated with tumor development and progression. Meanwhile, increased ADA activity may be a compensatory mechanism against the massive accumulation of its substrates (adenosine or deoxyadenosine), since increased proliferation leads to the salvage of nucleosides [55,56]. In addition, one possible reason for elevated levels of LDH could be its critical role in glycolysis [57].…”
Section: Discussionmentioning
confidence: 99%
“…In human tissues, adenosine deaminase is present as two isoenzymes: ADA1 and ADA2. [ 4 ] ADA1 constitutes the majority of ADA activity and it is present in virtually all tissues, with the highest levels in lymphoid cells, red blood cells and endothelium [ 4 , 5 ]. In addition to cytosolic form, ADA1 can be found as an ecto-enzyme binding to the cell surface by CD26 protein or adenosine receptors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%